2021
DOI: 10.3390/electronics10192354
|View full text |Cite
|
Sign up to set email alerts
|

Human Face Detection Techniques: A Comprehensive Review and Future Research Directions

Abstract: Face detection, which is an effortless task for humans, is complex to perform on machines. The recent veer proliferation of computational resources is paving the way for frantic advancement of face detection technology. Many astutely developed algorithms have been proposed to detect faces. However, there is little attention paid in making a comprehensive survey of the available algorithms. This paper aims at providing fourfold discussions on face detection algorithms. First, we explore a wide variety of the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 242 publications
(323 reference statements)
0
13
0
Order By: Relevance
“…The paper concluded that feature-based face recognition algorithms achieved the highest recognition accuracy compared to appearance-based and soft computing-based algorithms, with a normalized rate of 95%. In a very recent review paper [8], a wide variety of face detection algorithms are divided into feature-based and image-based approaches. The authors provided a detailed description along with a comparative evaluation of all algorithms among the two categories.…”
Section: Introductionmentioning
confidence: 99%
“…The paper concluded that feature-based face recognition algorithms achieved the highest recognition accuracy compared to appearance-based and soft computing-based algorithms, with a normalized rate of 95%. In a very recent review paper [8], a wide variety of face detection algorithms are divided into feature-based and image-based approaches. The authors provided a detailed description along with a comparative evaluation of all algorithms among the two categories.…”
Section: Introductionmentioning
confidence: 99%
“…It was known for its capability of processing images extremely rapidly while achieving high detection rates [3]. Face detector is essential to almost all recent important applications based on face analysis, such as face image enhancement [4] , face recognition [5] [6], face identification [7], face verification, face alignment [8], face feature extraction [9], face emotion recognition, and gender classification. One of the popular applications used today in mobile devices is the snapchat (snapchat application apply filters to face but first it has to find the face, and this is obtained by using Viola-Jones).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in information and communication technologies over the past years have expanded the scope of application of human skin detection: face detection [1][2][3], visual tracking for surveillance [4], gesture recognition [5], image retrieval and filtering image contents on the web [6], face recognition system [7,8], to mention just a few examples.…”
Section: Introductionmentioning
confidence: 99%